A Community-Academic Partnership to Address Racial/Ethnic Health Disparities through Grant-Making. (November 2013) - Ramos, Michelle A.; Fox, Ashley; Simon, Ellen P.; Horowitz, Carol R.
Because they focus on culturally and contextually specific health determinants, participatory approaches are well-recognized strategies to reduce health disparities. Yet, few models exist that use academic and community members equally in the grant funding process for programs aimed at reducing and eliminating these disparities. In 2008, the Communities IMPACT Diabetes Center in East Harlem, New York, developed a partnered process to award grants to community groups that target the social determinants of diabetes-related disparities. Community and academic representatives developed a novel strategy to solicit and review grants. This approach fostered equality in decision-making and sparked innovative mechanisms to award 500, 000 in small grants. An evaluation of this process revealed that most reviewers perceived the review process to be fair; were able to voice their perspectives (and those perspectives were both listened to and respected); and felt that being reviewers made them better grant writers. Community-academic partnerships can capitalize on each group's strengths and knowledge base to increase the community's capacity to write and review grants for programs that reduce health disparities, providing a local context for addressing the social determinants of health.